A revised key to the lizards of Iran (Reptilia: Squamata: Lacertilia) - Nasrabadi, Reza; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar; Gharzi, Ahmad (Zootaxa, 2017)
During recent years several lizard taxa have been added to the faunal list of Iran. Descriptions and new records are scattered in different publications in the herpetological literature. We here present species accounts for 152 species belonging to 43 genera and 10 families up to July 2016. The most diverse family is Lacertidae with 9 genera, 49 species and 2 subspecies, followed by Gekkonidae with 13 genera and 43 species, Agamidae with 5 genera, 18 species and 4 subspecies, Scincidae with 7 genera, 18 species and 2 subspecies, Phyllodactylidae with 1 genus and 10 species, Sphaerodactylidae with 2 genera and 4 species, Varanidae with 1 genus, 3 species and 2 subspecies, Uromastycidae with 2 genera and 3 species, Eublepharidae with 1 genus and 3 species, and Anguidae with 2 genera and 2 species. The current paper provides a dichotomous key including all of the currently recognized lizards of Iran.